2018
DOI: 10.1108/jeee-06-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: entrepreneurship in conflict and post conflict

Abstract: Purpose Conflict environments are under researchers’ scope in many disciplines at micro and macro levels. This paper aims to steer towards finding out how literature addresses entrepreneurship in conflict contexts. In addition, this paper tries to ascertain the theoretical bases and main themes and issues that have been studied in this area, to map the current knowledge in a clear frame as an attempt to highlight gaps and weaknesses in relevant literature. Design/methodology/approach Review entrepreneurship,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 70 publications
2
53
0
2
Order By: Relevance
“…Furthermore, the study has implications for a range of stakeholders including policymakers, mobile companies, mobile application developers, banks and financial institutions in post-conflict economies. Hence, our study advances the views expressed by scholars who emphasised the need to study entrepreneurship in post conflict economies (e.g., Aldairany et al, 2018 ; Brück et al, 2013 ). This is the first study to provide a holistic synthesis of the challenges facing women entrepreneurs in a country of high risk of instability and a post conflict economy (i.e., Iraq).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the study has implications for a range of stakeholders including policymakers, mobile companies, mobile application developers, banks and financial institutions in post-conflict economies. Hence, our study advances the views expressed by scholars who emphasised the need to study entrepreneurship in post conflict economies (e.g., Aldairany et al, 2018 ; Brück et al, 2013 ). This is the first study to provide a holistic synthesis of the challenges facing women entrepreneurs in a country of high risk of instability and a post conflict economy (i.e., Iraq).…”
Section: Introductionsupporting
confidence: 77%
“…Therefore, further investigation into Iraq’s local markets and national economy are critical to better understand how entrepreneurship will play a role in the country’s recovery (Brück et al, 2013 ). Furthermore, employing qualitative methods (e.g., interviews or case studies) could play a substantial role in understanding entrepreneurship in regions like Iraq (Aldairany et al, 2018 ). Conducting semi-structured interviews can provide a higher level of generalisability of the results in comparison to case studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some entrepreneurs have had to momentarily close their businesses due to government restrictions. In the pandemic situation, entrepreneurial activities may have experienced disruption in relation to decision making (Chell, 2013;Kuckertz et al, 2020;Turner & Akinremi, 2020); communication and conflict management (Aldairany et al, 2018); and well-being and entrepreneurial output (Stephan, 2018;Wach et al, 2016). We conducted the F I G U R E 1 Conceptual model of the study online survey complying with the social distancing policy of the government of Pakistan.…”
Section: Respondents Data Collection and Sample Sizementioning
confidence: 99%
“…It is known that a torn society is not a supportive environment for doing business since it leads to higher business costs (Williams and Vorley, 2017). According to a systematic review done using studies in uncertain environments, Aldairany et al (2018) concluded that these challenges mainly include lack of skilled and experienced human capital, absence of training, weak infrastructure and transportation, weak government support, unstable regulations, weak law and protection, poor financial systems and support, poor access to funds, markets, and networks and high levels of corruption. Moreover, MSMEs in torn societies face political instability (Desai, 2011; Khalique, Isa and Shaari, 2011; Muhammad et al , 2016; Williams and Vorley, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%